2003
DOI: 10.1258/096914103321610798
|View full text |Cite
|
Sign up to set email alerts
|

Review: Screening for vulnerability to psychological disorders in the military: an historical survey

Abstract: Although well-measured variables, such as intelligence, have been shown to predict success in training and aptitude, no instrument has yet been identified which can accurately assess psychological vulnerability. Previous attempts have failed because of false-positives, false-negatives and reluctance in the target population because of stigma. Early findings suggest that psychological surveillance, if not screening, may yield valuable results when applied to military populations exposed to stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 55 publications
(48 reference statements)
1
45
0
1
Order By: Relevance
“…during recruit selection or pre/post operational deployment. [4][5][6] The acceptability of a screening programme to the target population has also previously been raised, [7][8][9] but the reasons for low acceptability from the perspective of those invited to participate has been infrequently addressed. Service personnel, like their civilian counterparts, are not passive recipients of healthcare, and if they do not accept or have confidence in the service being provided, the screening programme will not be effective.…”
mentioning
confidence: 99%
“…during recruit selection or pre/post operational deployment. [4][5][6] The acceptability of a screening programme to the target population has also previously been raised, [7][8][9] but the reasons for low acceptability from the perspective of those invited to participate has been infrequently addressed. Service personnel, like their civilian counterparts, are not passive recipients of healthcare, and if they do not accept or have confidence in the service being provided, the screening programme will not be effective.…”
mentioning
confidence: 99%
“…It appears that, currently, applicants are not screened specifically for vulnerability to PTSD due to lack of evidence on screening for this purpose (Jones, Hyams, and Wessely 2003;Rona et al 2005). However, the screening instruments are used to filter out applicants with a current psychological disorder as well as those who seem to be unfit for military service for other reasons (Jones, Hyams, and Wessely 2003;Rona et al 2005).…”
Section: The Military Ptsd-infrastructure and Its Institutional Narramentioning
confidence: 99%
“…World War 1 onwards and found that the sensitivity and specificity of screening were low in relation to both future performance as a soldier and prediction of mental vulnerability 19 . In a questionnaire-based study of UK personnel deployed to the Iraq war, Rona et al…”
Section: 'Healthy Workers' and 'Less Healthy Leavers'mentioning
confidence: 99%